American methodist worship. - Tucker, Karen B. Westerfield (Religion in America series (Oxford University Press), 2001)
THis is an examination of Methodist practice, tracing its evolution from the earliest days up to the present. The author investigates the various rites and seasons of worship in Methodism and examines them in relation to American society.